Simultaneous recording of neuronal discharge and calcium activity reveals claustrum-cortex neurosynchrony under anesthesia - Penghui Fan; Rujin Zhang; Guihua Xiao; Yilin Song; Chaowei Zhuang; Lekang Yuan; Fan Mo; Botao Lu; Zhaojie Xu; Yiding Wang; Jinping Luo; Mixia Wang; et al. (Fundamental Research)
Neural information transmission between deep brain nuclei and the cortex is essential for brain function. Currently, high-resolution simultaneous detection of neural information between the deep brain nuclei and the large-scale cortex still poses challenges. We have developed the microelectrode arrays based on the Micro-Electro-Mechanical System technology, and modified the electrode surface with nanomaterials to improve the electrode performance. This study combined microelectrode arrays and extended-field-of-view microscopy to achieve simultaneous recording of claustrum (CLA) electrophysiology and wide-field cortical calcium imaging at single-cell resolution. This work investigated the synchronous changes of neural information in CLA and cortex of mice during the whole process from wakefulness to anesthesia and then to wakefulness, and summarized the characteristics of the CLA electrophysiology and cortical calcium signaling under different inhalation anesthesia concentrations. We found the synergy between microscopic spike and local field potential of CLA neurons under deep anesthesia, and the law that high inhalation anesthesia concentration enhanced the synchronization between neurons in CLA and cortex. The combination of microelectrode arrays and extended-field-of-view microscopy also gives a new method for synchronous detection of multimodal and multi-brain region neural information.